Development of durable fiber reinforced polymer grouted splice connection - Koushfar, Kiarash (2011)
Presently, the ease of field assembly offered by precast concrete systems is weighted against the larger numbers of connections that are required in precast concrete systems, which pose a problem. In this regard, grouted splice sleeve connections are gaining popularity. However, the existing splice sleeve connectors in the market are proprietary and patented by foreign companies resulting in the high cost of adaption, particularly in Malaysia. Over the last few years, the use of composite materials has become an increasingly popular method of repairing and strengthening ageing civil engineering structures. The primary cause of corrosion in steel joint connectors is exposure to sodium chloride that is present in marine environments or de-icing salts that are applied to bridge decks and parking structures. This research aims to use durable and non-corrosive FRP connections as alternatives to current steel precast connection methods. The development of an FRP connection component will benefit the precast industry, FRP manufacturers, contractors and owners. This research follows the method of grouted splice sleeve connectors. This new type of connector is an alternative method for connecting precast concrete structural members with non-metallic FRP components to provide the continuity between two separate steel bars in precast structures. Durable and non-corrosive FRP connection is efficient and economical alternatives to current steel precast connection methods. Since there is no need to modify the internal surface of the sleeve and to use threaded connection between reinforcement bar and sleeve, the newly developed FRP connector can be easily produced as a single unit compared to the conventional grouted pipe connectors. All it requires is a tapered FRP sleeve to connect reinforcement bars. This project summarizes the experimental program and also the performance of the newly developed FRP splice connector under axial tension. The influence of several parameters of the proposed connector is identified. These parameters include the incorporation of the tapered FRP sleeve, internal diameter of the mid-length of the FRP connector, and number of wrapping FRP layers. The experiments examined the tensile strength as well as the failure mode of the connectors. The results of this research prove successfully that the invention of a non-metallic FRP connector used for precast concrete construction is possible by using FRP material as the conventional steel pipes. By using the newly developed FRP connectors in the precast construction industry, the service life of the connections increase due to the FRP material properties and elimination of the steel components in structures which reduce the life cost of the structures.